ZDR-1 v luči novejše sodne prakse - Kogej Dmitrovič, Biserka (Podjetje in delo, 2016)
The article presents the new judicial practice according to Employment Relationship Act (Zakon o delovnih razmerjih - ZDR-1). Decisions of the supreme court and positions regarding the changed provisions of ZDR-1 in regards to ZDR are presented, as well as new positions, the foundation of which is not the changed legislation, but the deviation from current judicial practice. Decisions are also presented, wherein positions are adopted in regards to the serving of termination of the employment contract, form and content of the termination of contract, and the obligations of the employer before such termination, relating to a written warning of the employee with the apparent reason of incompetence, or violations and the right to defend. The position of judicial practice is shown, wherein the employer may remove the violations, due to which an employee may exceptionally terminate the employment contract. According to ZDR-1, the employer may regularly terminate an employment contract due to unsuccessful trial work, immediately after finding out, that the employee does not suit the demands of the work place, but must ensure a period of notice; the arrangement differs from ZDR. Decisions are presented in disputes regarding the existence of work relationship, whereby the judicial practice has changed, so that these disputes do not demand the identification of illegality of the employment contract termination any more.
Keywords: delovna razmerja; delovni spor; delovno pravo; pogodba o zaposlitvi